Information, Communication, and History - Bermejo Barrera, José Carlos (Historiografías, 2022)
In this article we shall suggest a pattern in which, taking the concept of mode of information as starting point, three different systems concerning its production, transmission, and social circulation are to set up. This includes: the mode of culture exclusively oral, that of written cultures, and that of information and communication systems based upon electronic and digital supports. Each one of them is capable to generate its own configuration model of social memory, and thus a possible approach to the past, the social memory being the one that gives raise to collective identities and allows to integrate the individual into the group. The approaches to the past depend partially upon available research techniques, but is the mode of information the only one that permits or not their development. Starting from this model, it is suggested that the only way out to defend the importance of history and social sciences, is to regard them as fundamental models capable of examining the information into the present, due to fact that the great amount of that information comes from the past. Keywords Mode of information, social communication systems, collective memory, collective identities, functions of history